Influence of polypyrrole nanospheres on the direct current dielectric properties of LDPE. Issue 7 (10th May 2021) - Zhang, Chengcheng; Ren, Qiang; Cheng, Dahu; Li, Chunyang; Yang, Jiaming; Zhao, Hong
Abstract: To study the effect of nano conducting materials on the direct current (DC) dielectric properties of low density polyethylene (LDPE), polypyrrole nanospheres are prepared by the soft template method and then melt‐blended with LDPE to obtain LDPE/polypyrrole nanocomposites. The micro‐structure, space charge distribution, thermally stimulated depolarization current, DC conductivity and DC breakdown strength of the nanocomposites are investigated. The results show there is interaction between polypyrrole nanospheres and LDPE, which will not affect the crystal structure of LDPE, but slightly increase the crystallinity of LDPE/polypyrrole nanocomposites. Polypyrrole nanospheres can introduce deep traps in LDPE to capture space charge carriers, which will suppress the accumulation of space charges in LDPE and reduce the DC conductivity. The DC breakdown strength of LDPE/polypyrrole nanocomposites is improved slightly by adding a small amount of polypyrrole nanospheres. Abstract :